2016
DOI: 10.4103/0971-5851.195734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of areca nut chewing and maximal mouth opening in schoolgoing children in Ahmedabad

Abstract: Context:Areca nut is chewed by itself and in various scented preparations. Areca nut chewing is widely practiced in many parts of Asia, including India. Users often consider it harmless and report a sense of well-being, but evidence has shown that it is far from harmless and can have multiple oral health implications such as oral submucosal fibrosis posing difficulty in opening mouth and carcinogenesis. Studies in India have reported increasing prevalence of this habit among schoolgoing children. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…OSMF is one of the most common premalignant conditions of the oral cavity, affecting more than five million people globally, and is predominantly seen among the South and Southeast Asian subcontinent population with a prevalence of 0. , in their epidemiological studies, observed higher OSMF instances among the young to middle-aged groups and school-going children, with a higher male predilection owing to habit addiction [22][23][24][25].…”
Section: Epidemiological Considerationsmentioning
confidence: 89%
See 1 more Smart Citation
“…OSMF is one of the most common premalignant conditions of the oral cavity, affecting more than five million people globally, and is predominantly seen among the South and Southeast Asian subcontinent population with a prevalence of 0. , in their epidemiological studies, observed higher OSMF instances among the young to middle-aged groups and school-going children, with a higher male predilection owing to habit addiction [22][23][24][25].…”
Section: Epidemiological Considerationsmentioning
confidence: 89%
“…Khan AM et al, Jain A et al, Kumar KK et al, and Hazarey VK et al, in their epidemiological studies, observed higher OSMF instances among the young to middle-aged groups and school-going children, with a higher male predilection owing to habit addiction [ 22 - 25 ].…”
Section: Reviewmentioning
confidence: 99%